Laminate film

JP2025011543A5Active Publication Date: 2025-01-31NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023113722
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-31
Estimated Expiration
2043-07-11

AI Technical Summary

Benefits of technology

【0013】 本発明の積層フィルムにおいては、上記のように、積層フィルムの厚さ方向の断面視における、基材フィルムと密着層との界面における第1界面長に対する、密着層と無機物層との界面における第2界面長の比率が、1.10以上である。このような積層フィルムにおいては、第1および第2界面長の上記比率が1.10以上であることにより、無機物層に対する密着層のアンカー効果が発揮され、基材フィルムに対する密着層を介した無機物層の密着性を確保できる。そのため、基材フィルムの密着層側の表層における、ナノシリカ粒子などの粒子の含有量を、低減できる。これにより、積層フィルムの製造コストを低減できる。したがって、本発明の積層フィルムによると、製造コストを抑制しつつ基材フィルムに対する無機物層の密着性を確保できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a laminate film capable of securing adhesiveness of an inorganic material layer to a substrate film while suppressing the production cost.SOLUTION: There is provided a laminate film X comprising a substrate film 10, an adhesion layer 21 on the substrate film 10 and an inorganic material layer 22 on the adhesion layer 21. In a cross-sectional view of the laminate film X in the thickness direction H, the ratio of a second interface length L2 at the interface between the adhesion layer 21 and the inorganic material layer 22 to the first interface length L1 at the interface between the substrate film 10 and the adhesion layer 21 is 1.10 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated film. [Background technology]

[0002] From the viewpoint of weight reduction and high performance of electronic products, various composite materials in which organic materials and inorganic materials are combined have been developed. For example, a laminated film having a base film made of an organic material and an inorganic layer on the base film is known as a composite material. In the manufacturing process of the laminated film, for example, before the inorganic layer is formed on the base film, the surface of the base film is plasma treated to remove dirt and moisture from the surface. Removal of dirt and moisture from the surface of the base film helps to increase the adhesion of the inorganic layer formed on the surface to the base film. Technology related to such laminated films is described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-65437 Summary of the Invention [Problem to be solved by the invention]

[0004] Patent Document 1 describes a laminated film as an anti-reflection film. This laminated film includes a base film, an adhesive layer, and an inorganic layer as an anti-reflection layer in this order in the thickness direction. The base film has a hard coat (HC) layer on the adhesive layer side. This HC layer contains nanosilica particles. As a result, the HC layer has surface irregularities on the adhesive layer side. The adhesiveness of the inorganic layer to the base film is increased by the anchor effect due to the surface irregularities of the HC layer and the physicochemical action of the adhesive layer. If the adhesiveness of the inorganic layer to the base film is insufficient, the inorganic layer will peel off from the base film.

[0005] However, nanosilica particles are relatively expensive and increase the manufacturing costs of the laminated film.

[0006] The present invention provides a laminate film that can ensure adhesion of an inorganic layer to a substrate film while suppressing production costs. [Means for solving the problem]

[0007] The present invention [1] includes a laminate film comprising a base film, an adhesive layer on the base film, and an inorganic layer on the adhesive layer, in which, in a cross-sectional view in the thickness direction of the laminate film, the ratio of a second interface length at the interface between the adhesive layer and the inorganic layer to a first interface length at the interface between the base film and the adhesive layer is 1.10 or more.

[0008] The present invention [2] includes the laminate film according to the above [1], in which the ratio is 2.0 or less.

[0009] The present invention [3] includes the laminate film according to the above [1] or [2], wherein the adhesion layer has a thickness of 1 nm or more and 50 nm or less.

[0010] The present invention [4] includes the laminate film according to any one of the above [1] to [3], wherein the adhesion layer is an inorganic oxide film containing at least one element selected from the group consisting of Si, In, Al, Sn, Ti, Zr and Nb.

[0011] The present invention [5] includes the laminate film according to any one of the above [1] to [4], in which the inorganic layer includes a conductive layer.

[0012] The present invention [6] includes the laminate film according to any one of the above [1] to [5], wherein the inorganic layer includes an antireflection layer, and the antireflection layer includes a plurality of transparent inorganic oxide films stacked in the thickness direction. Effect of the Invention

[0013] In the laminated film of the present invention, as described above, the ratio of the second interface length at the interface between the adhesive layer and the inorganic layer to the first interface length at the interface between the base film and the adhesive layer in the cross-sectional view in the thickness direction of the laminated film is 1.10 or more. In such a laminated film, the ratio of the first and second interface lengths is 1.10 or more, so that the anchor effect of the adhesive layer to the inorganic layer is exerted, and the adhesion of the inorganic layer to the base film via the adhesive layer can be ensured. Therefore, the content of particles such as nanosilica particles in the surface layer on the adhesive layer side of the base film can be reduced. This allows the manufacturing cost of the laminated film to be reduced. Therefore, according to the laminated film of the present invention, the adhesion of the inorganic layer to the base film can be ensured while suppressing the manufacturing cost. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a laminated film of the present invention. [Diagram 2] The laminate film shown in FIG. 1 has an antireflection layer as an inorganic layer. [Diagram 3] 3 shows an example of a method for producing the laminated film shown in Fig. 1. Fig. 3A shows a cured resin layer forming step, Fig. 3B shows an adhesion layer forming step, and Fig. 3C shows an inorganic layer forming step. [Figure 4] 2 is a schematic diagram of an apparatus for carrying out a plasma treatment step and a film formation step in the example of the method for producing the laminated film shown in FIG. 1. FIG. [Diagram 5] 5 is a perspective view showing the positional relationship between a low inductance antenna and a base film in the plasma processing chamber shown in FIG. [Figure 6] 5 is a cross-sectional view showing the positional relationship between a low inductance antenna and a base film in the plasma processing chamber shown in FIG. [Figure 7] 3 is a schematic diagram of an observation image of a cross section of a sample in Example 1. FIG. [Figure 8] 1 is a schematic diagram of an observation image of a cross section of a sample in Comparative Example 1. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] As shown in Fig. 1, a laminated film X according to one embodiment of the present invention includes a base film 10, an adhesive layer 21, and an inorganic layer 22 in this order in a thickness direction H. The laminated film X extends in a direction (plane direction D) perpendicular to the thickness direction H. The laminated film X is, for example, an anti-reflection film or a transparent conductive film. The laminated film X may be another type of film.

[0016] In this embodiment, the base film 10 includes a resin film 11 and a cured resin layer 12 in this order in the thickness direction H. In this embodiment, the resin film 11 and the cured resin layer 12 are in contact with each other. In the base film 10, the cured resin layer 12 forms a first surface 10a, and the resin film 11 forms a second surface 10b.

[0017] The resin film 11 is an element that ensures the strength of the laminated film X. The resin film 11 is, for example, a transparent resin film having flexibility. Examples of the material of the resin film 11 include polyester resin, polyolefin resin, cellulose resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of the cellulose resin include triacetyl cellulose (TAC). These materials may be used alone, or two or more types may be used in combination. From the viewpoint of transparency and strength, the material of the resin film 11 is preferably at least one selected from the group consisting of polyester resin, polyolefin resin, and cellulose resin, and more preferably at least one selected from the group consisting of PET, COP, and TAC. In addition, the resin film 11 does not contain particles in this embodiment.

[0018] The thickness of the resin film 11 is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, and is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. When the thickness of the resin film 11 is equal to or more than the above lower limit, the strength of the laminated film X can be ensured. When the thickness of the resin film 11 is equal to or less than the above upper limit, the handleability of the base film 10 in the roll-to-roll process described below can be ensured. In addition, a carrier film may be attached to the second surface 10b of the resin film 11 in order to ensure the transportability and handleability of the base film 10 in the roll-to-roll process.

[0019] The total light transmittance (JIS K 7375:2008) of the resin film 11 is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, and is, for example, 100% or less. When the total light transmittance of the resin film 11 is equal to or more than the above lower limit, good transparency can be ensured in the laminate film X.

[0020] The cured resin layer 12 is a functional layer containing a resin. Specifically, the cured resin layer 12 is a cured product of a curable resin composition containing a curable resin. An example of the functional layer is a hard coat layer. The hard coat layer is a layer that makes it difficult for scratches to form on the exposed surface (upper surface in FIG. 1) of the inorganic layer 22.

[0021] Examples of the curable resin include polyester resin, acrylic urethane resin, acrylic resin (excluding acrylic urethane resin), urethane resin (excluding acrylic urethane resin), amide resin, silicone resin, epoxy resin, and melamine resin. These curable resins may be used alone or in combination of two or more. From the viewpoint of ensuring the hardness of the cured resin layer 12, the curable resin is preferably at least one selected from the group consisting of acrylic urethane resin and acrylic resin.

[0022] Examples of the curable resin include ultraviolet curable resin and thermosetting resin. The curable resin is preferably an ultraviolet curable resin. When the curable resin is an ultraviolet curable resin, the curable resin can be cured without high temperature heating, so that the production efficiency of the laminated film X can be improved.

[0023] When the base film 10 has a cured resin layer 12, it is preferable that the cured resin layer 12 contains fewer inorganic oxide particles. The fewer the inorganic oxide particles in the cured resin layer 12, the more the scattering of light incident on the laminated film X caused by particles in the base film 10 can be suppressed, and the manufacturing cost of the laminated film X can be reduced. Examples of materials for inorganic oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. The content of inorganic oxide particles in the cured resin layer 12 is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, even more preferably 1% by mass or less, even more preferably 0.5% by mass or less, even more preferably 0.2% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0.0% by mass.

[0024] The thickness of the cured resin layer 12 is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more, and is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. When the thickness of the cured resin layer 12 is equal to or more than the above lower limit, the function of the cured resin layer 12 can be ensured. Specifically, when the cured resin layer 12 is a hard coat layer, the scratch resistance of the inorganic layer 22 can be ensured. When the thickness of the cured resin layer 12 is equal to or less than the above upper limit, the transparency of the cured resin layer 12 can be ensured.

[0025] The total light transmittance (JIS K 7375:2008) of the base film 10 is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, and is, for example, 100% or less. When the total light transmittance of the base film 10 is equal to or more than the above lower limit, good transparency can be ensured in the laminate film X.

[0026] The surface roughness Sa (arithmetic mean height based on ISO 25178-2:2012) of the first surface 10a of the base film 10 is preferably 1.0 nm or more, more preferably 1.2 nm or more, even more preferably 1.3 nm or more, and is preferably 10.0 nm or less, more preferably 7.0 nm or less, even more preferably 4.5 nm or less. When the surface roughness Sa of the first surface 10a is equal to or more than the above lower limit, the fine irregularities of the first surface 10a have an anchoring effect on the adhesive layer 21, thereby enhancing the adhesion of the inorganic layer 22 to the base film 10 via the adhesive layer 21. When the surface roughness Sa of the first surface 10a is equal to or less than the above upper limit, excessive irregularities at the interface in the inorganic layer 22 described below can be suppressed.

[0027] The first surface 10a is, for example, a surface that has been plasma-treated. The plasma treatment is preferably a treatment by inductively coupled plasma using an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna (oxygen-LAICP treatment). The oxygen-LAICP treatment of the first surface 10a will be described later in detail with respect to the manufacturing method of the laminated film X.

[0028] The adhesive layer 21 is disposed on one surface of the base film 10 in the thickness direction H. Specifically, the adhesive layer 21 is disposed on the first surface 10a of the base film 10. The adhesive layer 21 is in contact with the base film 10. The adhesive layer 21 is a layer that enhances the adhesiveness of the inorganic layer 22 to the base film 10. Examples of materials for the adhesive layer 21 include metals such as Si, In, Ni, Cr, Ar, Sn, Au, Ag, Pt, Zn, Ti, W, Zr, Nb, and Pd, alloys of two or more of these metals, and oxides of these metals. From the viewpoint of achieving both adhesiveness to both the base film 10 and the inorganic layer 22 and transparency of the adhesive layer 21, the adhesive layer 21 is preferably an inorganic oxide film containing at least one element selected from the group consisting of Si, In, Al, Sn, Ti, Zr, and Nb. From the viewpoint of achieving both adhesion to both the base film 10 and the inorganic layer 22, and transparency of the adhesion layer 21, indium tin composite oxide (ITO) or silicon oxide (SiOx) is more preferable as the material of the adhesion layer 21. The silicon oxide as the material of the adhesion layer 21 is preferably SiOx having a smaller amount of oxygen than the stoichiometric composition, and more preferably SiOx where x is 1.2 or more and 1.9 or less.

[0029] The thickness of the adhesive layer 21 is preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 3 nm or more, and is preferably 50 nm or less, more preferably 30 nm or less, even more preferably 10 nm or less, and even more preferably 5 nm or less. When the thickness of the adhesive layer 21 is equal to or more than the above lower limit, the adhesive strength between the base film 10 and the inorganic layer 22 can be ensured. When the thickness of the adhesive layer 21 is equal to or less than the above upper limit, the transparency of the adhesive layer 21 can be ensured.

[0030] The inorganic layer 22 is disposed on one surface of the adhesive layer 21 in the thickness direction H. The inorganic layer 22 is in contact with the adhesive layer 21. Examples of the inorganic layer 22 include an anti-reflection layer and a conductive layer. The anti-reflection layer is a layer having anti-reflection properties that suppresses the reflection intensity of external light. The conductive layer is a layer having conductivity. The inorganic layer 22 may be another layer. The inorganic layer 22 may also be a composite layer including an anti-reflection layer and another layer. The inorganic layer 22 may also be a composite layer including a conductive layer and another layer.

[0031] The inorganic layer 22 as an antireflection layer preferably includes a plurality of transparent inorganic oxide films laminated in the thickness direction H. FIG. 2 shows an example of such an inorganic layer 22. The inorganic layer 22 (antireflection layer) in FIG. 2 includes a high refractive index layer 22a, a low refractive index layer 22b, a high refractive index layer 22c, and a low refractive index layer 22d in this order from the adhesive layer 21 side in the thickness direction H. The high refractive index layer 22a contacts the adhesive layer 21. The high refractive index layer 22a contacts the low refractive index layer 22b. The low refractive index layer 22b contacts the high refractive index layer 22c. The high refractive index layer 22c contacts the low refractive index layer 22d. The high refractive index layers 22a and 22c are layers with a relatively high refractive index, and the low refractive index layers 22b and 22d are layers with a relatively low refractive index. In such a laminated structure, the intensity of the reflected light is attenuated by the interference between the reflected light at multiple interfaces in the high refractive index layers 22a, 22c and the low refractive index layers 22b, 22d. Such interference can be realized by adjusting the optical film thickness (the product of the refractive index and the thickness of the film) of each layer of the inorganic layer 22.

[0032] The high refractive index layer 22a (first high refractive index layer) is made of a high refractive index material having a refractive index of preferably 1.9 or more at a wavelength of 550 nm. Examples of the high refractive index material include niobium oxide (Nb 2 O 5 ), titanium oxide, zirconium oxide, indium tin oxide (ITO), and antimony tin oxide (ATO). From the viewpoint of achieving both a high refractive index and low absorption of visible light, the high refractive index material is preferably niobium oxide (refractive index 2.33). The optical film thickness of the high refractive index layer 22a is, for example, 20 nm or more and, for example, 55 nm or less.

[0033] The low refractive index layer 22b (first low refractive index layer) is made of a low refractive index material having a refractive index of preferably 1.6 or less at a wavelength of 550 nm. Examples of low refractive index materials include silicon dioxide (SiO 2 ) and magnesium fluoride. From the viewpoint of achieving both a low refractive index and low absorption of visible light, the low refractive index material is preferably silicon dioxide (refractive index 1.46). The optical film thickness of the low refractive index layer 22b is, for example, 15 nm or more and, for example, 70 nm or less.

[0034] The high refractive index layer 22c (second high refractive index layer) is made of a high refractive index material having a refractive index of preferably 1.9 or more at a wavelength of 550 nm. Examples of the high refractive index material include the materials described above for the high refractive index layer 22a, and niobium oxide is preferred. The optical thickness of the high refractive index layer 22c is, for example, 60 nm or more and, for example, 330 nm or less.

[0035] The low refractive index layer 22d (second low refractive index layer) is made of a low refractive index material having a refractive index of preferably 1.6 or less at a wavelength of 550 nm. Examples of the low refractive index material include the materials described above for the low refractive index layer 22b, and silicon dioxide is preferred. The optical thickness of the low refractive index layer 22d is, for example, 100 nm or more and, for example, 160 nm or less.

[0036] The total thickness of the inorganic layer 22 as an antireflection layer is preferably 180 nm or more, more preferably 200 nm or more, and even more preferably 220 nm or more, and is preferably 320 nm or less, more preferably 280 nm or less, and even more preferably 250 nm or less. In this embodiment, the total thickness of the inorganic layer 22 as an antireflection layer is the sum of the thicknesses of the high refractive index layers 22a, 22c and the low refractive index layers 22b, 22d. When the total thickness of the inorganic layer 22 is equal to or greater than the lower limit, the inorganic layer 22 can ensure the function of attenuating the reflected light intensity. When the total thickness of the inorganic layer 22 is equal to or less than the upper limit, cracking of the inorganic layer 22 can be suppressed.

[0037] The inorganic layer 22 as a conductive layer is formed from a conductive material. Examples of conductive materials include metals and metal oxides. Examples of metals include copper, silver, gold, nickel, chromium, and alloys thereof. Examples of metal oxides include indium-containing conductive oxides and antimony-containing conductive oxides. Examples of indium-containing conductive oxides include indium tin composite oxide (ITO), indium zinc composite oxide (IZO), indium gallium composite oxide (IGO), and indium gallium zinc composite oxide (IGZO). Examples of antimony-containing conductive oxides include antimony tin composite oxide (ATO).

[0038] The inorganic layer 22 has a surface 22A on the opposite side to the base film 10. The surface roughness Sa (arithmetic mean height based on ISO 25178-2:2012) of the surface 22A is preferably 4.5 nm or less, more preferably 3.0 nm or less, even more preferably 2.5 nm or less, even more preferably 2.0 nm or less, and even more preferably 1.7 nm or less. When the surface roughness Sa of the surface 22A is equal to or less than the upper limit, light scattering on the surface 22A can be suppressed. In addition, the surface roughness Sa of the surface 22A is preferably 1.0 nm or more, more preferably 1.3 nm or more, even more preferably 1.5 nm or more, and even more preferably more than 1.5. When the surface roughness Sa of the surface 22A is equal to or more than the lower limit, the frictional force on the surface 22A can be reduced, and for example, good transportability of the laminated film X can be ensured in the manufacturing method of the laminated film X by the roll-to-roll method. The method for measuring the surface roughness Sa is as described below in the examples.

[0039] In a cross-sectional view in the thickness direction H of the laminated film X, the interface between the base film 10 and the adhesive layer 21 has fine irregularities (not shown). The interface between two adjacent layers in the inorganic layer 22 also has fine irregularities (not shown). The microscopic irregularities are, for example, irregularities on the order of nanometers. In a cross-sectional view in the thickness direction H of such a laminated film X, the ratio (L2 / L1) of the second interface length L2 at the interface (second interface) between the adhesive layer 21 and the inorganic layer 22 to the first interface length L1 at the interface (first interface) between the base film 10 and the adhesive layer 21 is 1.10 or more, preferably 1.20 or more, more preferably 1.30 or more, and even more preferably 1.35 or more. The first interface length L1 is the length of the first interface included in a range of, for example, 70 nm in the plane direction D in one cross-sectional view. The second interface length L2 is the length of the second interface included in the same range in the plane direction D in the same cross-sectional view. The method for measuring the first interface length L1 and the second interface length L2 is as described later in the examples. When the ratio (L2 / L1) is equal to or greater than the lower limit, the adhesion of the inorganic layer 22 in the laminated film X can be increased by the anchor effect. The ratio (L2 / L1) is preferably equal to or less than 2.00, more preferably equal to or less than 1.70, and more preferably equal to or less than 1.50. When the ratio (L2 / L1) is equal to or less than the upper limit, the surface roughness Sa of the surface 22A of the inorganic layer 22 can be suppressed. When the inorganic layer 22 is an anti-reflection layer, the suppression of the surface roughness Sa of the surface 22A can suppress light scattering on the surface 22A. Examples of methods for adjusting the ratio (L2 / L1) include adjusting the amount of oxygen gas introduced in the oxygen-LAICP treatment process, adjusting the frequency of the high-frequency power in the high-frequency power source, adjusting the magnitude of the applied power, and adjusting the treatment time.

[0040] The second interface length L2 is preferably 90 nm or more, more preferably 100 nm or more, even more preferably 110 nm or more, and even more preferably 115 nm or more, and is preferably 160 nm or less, more preferably 140 nm or less, and even more preferably 130 nm or less. When the second interface length L2 is the above-mentioned lower limit or more, the adhesion of the inorganic layer 22 to the base film 10 via the adhesion layer 21 can be improved. When the second interface length L2 is the above-mentioned upper limit or less, the roughness of the surface 22A of the inorganic layer 22 can be adjusted.

[0041] The peeling rate of the inorganic layer 22 of the laminated film X in the second test described below after the first test (accelerated weather resistance test) described below is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less, from the viewpoint of ensuring the adhesion of the inorganic layer 22. More specifically, the methods of the first and second tests are as described later in the examples. When the peeling rate of the inorganic layer 22 is equal to or less than the upper limit, it is possible to suppress a substantial decrease in the function of the inorganic layer 22 due to peeling of the inorganic layer 22.

[0042] Test 1: First, the side of the base film 10 of the laminated film X is fixed to a glass plate. Next, the inorganic layer 22 of the laminated film X on the glass plate is irradiated with light at a temperature of 85° C., a relative humidity of 45%, and an irradiation intensity (integrated illuminance at 290 nm to 450 nm) of 150 mW / cm 2 2 The specimen is exposed to light for 32.5 hours under the above conditions.

[0043] Test 2: First, eleven parallel first incisions (1 mm apart) extending linearly in a first direction and eleven parallel second incisions (1 mm apart) extending linearly in a second direction perpendicular to the first direction are formed with a cutter knife in the inorganic layer 22 and the adhesive layer 21 of the laminated film X on the glass plate after the first test, and 100 grids are formed by the first and second incisions. Next, isopropyl alcohol is continuously dropped at 2 mL / min on the 100 grid areas of the laminated film X, while a polyester wiper is slid over the area with a wiper contact surface of 20 mm x 20 mm, a load of 1.5 kg / 20 mm, a sliding speed of 50 mm / sec, and 1000 reciprocations. Next, 0.25 mm out of the 100 grids are cut. 2 The number of squares where the above peeling occurred is counted. The counted number is then divided by 100 to calculate the peeling rate (%).

[0044] In the laminated film X, as described above, the ratio (L2 / L1) of the second interface length L2 at the interface between the adhesive layer 21 and the inorganic layer 22 to the first interface length L1 at the interface between the base film 10 and the adhesive layer 21 in the cross-sectional view in the thickness direction H is 1.10 or more. In such a laminated film X, the ratio (L2 / L1) is 1.10 or more, so that the anchor effect of the adhesive layer 21 to the inorganic layer 22 is exerted, and the adhesiveness of the inorganic layer 22 to the base film 10 via the adhesive layer 21 can be ensured. Therefore, the content of particles such as nanosilica particles in the surface layer on the adhesive layer 21 side of the base film 10 can be reduced. This allows the manufacturing cost of the laminated film X to be reduced. Therefore, according to the laminated film X, the adhesiveness of the inorganic layer 22 to the base film 10 can be ensured while suppressing the manufacturing cost.

[0045] 3A to 3C show an example of a method for producing the laminated film X. This production method includes a cured resin layer forming step (FIG. 3A), a plasma treatment step, and a film forming step (FIGS. 3B and 3C).

[0046] In the cured resin layer forming step, as shown in FIG. 3A, a cured resin layer 12 is formed on a long resin film 11. This results in a substrate film 10. The cured resin layer 12 can be formed by applying the above-mentioned curable resin composition on the resin film 11 to form a coating film, and then curing the coating film. The curable resin composition may contain other components other than the above-mentioned curable resin as necessary. Examples of the other components include a solvent and a leveling agent. Examples of the solvent include butyl acetate, ethyl acetate, toluene, and cyclopentanone. When the curable resin composition contains an ultraviolet-curable resin as the curable resin, the curable resin composition preferably contains a photopolymerization initiator. When the curable resin composition contains a thermosetting resin as the curable resin, the curable resin composition preferably contains a thermal polymerization initiator.

[0047] When the curable resin composition contains a solvent, the coating film on the resin film 11 is dried after the application of the curable resin composition. The drying temperature is, for example, 50° C. or higher and, for example, 120° C. or lower. The drying time is, for example, 10 seconds or longer and, for example, 10 minutes or shorter.

[0048] When the curable resin composition contains an ultraviolet-curable resin, the coating film on the resin film 11 is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a high-pressure mercury lamp and an LED light. The cumulative irradiation amount of the ultraviolet light is, for example, 100 mJ / cm. 2 or more, for example, 500 mJ / cm 2 The following is the result.

[0049] When the curable resin composition contains a thermosetting resin, the coating on the resin film 11 is cured by heating. The heating temperature is, for example, 100° C. or more and, for example, 150° C. or less. The heating time is, for example, 10 seconds or more and, for example, 10 minutes or less.

[0050] In this manner, a long base film 10 can be produced. In this embodiment, a roll of the long base film 10 is prepared. Specifically, the base film 10 is wound so that the first surface 10a of the base film 10 faces inward in the roll radial direction.

[0051] In this manufacturing method, next, a plasma treatment process and a film formation process are carried out in sequence while the base film 10 is transported as a workpiece film W by a roll-to-roll method under a reduced pressure atmosphere. The device Y shown in Fig. 4 is an example of a device for carrying out the plasma treatment process and the film formation process. The device Y includes a payout chamber R1, a winding chamber R2, a connection chamber C1, a plasma treatment chamber C2, a connection chamber C3, a film formation chamber C4, a connection chamber C5, a connection chamber C6, and a PEM device (not shown).

[0052] The pay-out chamber R1 is equipped with a pay-out roller 51 for paying out the workpiece film W. A roll of a long base film 10 is attached to the pay-out roller 51 as the workpiece film W. In addition, a predetermined number of guide rollers G for guiding the workpiece film W are provided in the pay-out chamber R1.

[0053] The winding chamber R2 is equipped with a winding roller 52 for winding up the workpiece film W. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the winding chamber R2.

[0054] The connecting chamber C1 is disposed next to the pay-out chamber R1 in the running direction of the workpiece film W, and disposed before the plasma processing chamber C2. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C1. The connecting chamber C1 is connected to a vacuum pump (not shown), and is configured so that the pressure inside the connecting chamber C1 can be adjusted. When the device Y is in operation, the pressure inside the connecting chamber C1 is maintained at a predetermined pressure between the pressure inside the pay-out chamber R1 and the pressure inside the plasma processing chamber C2. This ensures a pressure difference between the pay-out chamber R1 and the plasma processing chamber C2.

[0055] The plasma processing chamber C2 is disposed between the connecting chamber C1 and the connecting chamber C3 in the running direction of the workpiece film W. In the plasma processing chamber C2, a plasma processing step is carried out as described below.

[0056] In this embodiment, the plasma processing chamber C2 is equipped with a plurality of low inductance antennas (LA) 71. The low inductance antenna means an antenna that has a low inductance of 7.5 μH or less and can generate inductively coupled plasma by applying high frequency power. In this embodiment, the LA 71 is supported by a mounting fixture 72 and covered by a cover block 73 (not shown in FIG. 5) as shown in FIG. 5 and FIG. 6, and is disposed inside the plasma processing chamber C2 (a case where the number of LA 71 is four is illustrated as an example).

[0057] The multiple LAs 71 are arranged in a line in the running direction of the base film 10 and in a direction perpendicular to the running direction (the width direction of the base film 10). The fixture 72 is a vacuum flange. The LAs 71 are fixed to the fixture 72 via a feedthrough 74 as shown in FIG. 6. The fixture 72 is assembled to an opening 75 provided in the wall of the plasma processing chamber C2 as shown in FIG. 4. Specifically, the fixture 72 is assembled to the opening 75 with a seal member (not shown) sandwiched between the wall of the plasma processing chamber C2 and the fixture 72. The LAs 71 are electrically connected to a high-frequency power source (RF power source) outside the plasma processing chamber C2 via an impedance matching device. Such an LAs 71 is formed of a conductor. Examples of the conductor include copper and silver, and copper is preferable. The LAs 71 may be covered with an insulator. Examples of the insulator include glass and quartz.

[0058] The cover block 73 includes a block body 73A and a plurality of partition plates 73B. The block body 73A has a plurality of storage spaces 73a. Each storage space 73a stores one LA 71. The partition plates 73B are arranged to close the storage spaces 73a. The storage spaces 73a are sealed spaces. In the cover block 73, the block body 73A is made of, for example, aluminum. Examples of aluminum include aluminum A5052. The partition plates 73B are made of an insulating material. Examples of insulating materials include quartz and glass. The separation distance d' (shown in FIG. 6) between the base film 10 traveling in the plasma processing chamber C2 and the cover block 73 is, for example, 50 to 200 mm. Such a cover block 73 helps to avoid damage and contamination of the LA 71 due to plasma processing without excessively reducing the plasma conversion efficiency due to the power applied to the LA 71, and also helps to suppress damage to the substrate film 10 being plasma processed.

[0059] As shown in FIG. 5, the LA71 has an open loop shape in this embodiment. The open loop shape of the LA71 is advantageous in lowering the inductance of the LA71. Therefore, the open loop shape of the LA71 can suppress an increase in voltage due to an increase in the power applied to the LA71. This can suppress abnormal discharge during the plasma processing described below. Suppression of abnormal discharge can suppress damage to the base film 10 being plasma processed. Specifically, the LA71 has a U-shape having two free ends. For each LA71, the two free ends are fixed to the mounting fixture 72 so as to be aligned in the width direction of the base film 10. In addition, in this embodiment, the LA71 has an extension portion 71a on the opposite side to the two free ends. The extension portion 71a extends parallel to the base film 10 passing through the plasma processing chamber C2. The extension portion 71a extends in the width direction of the base film 10. Each extension 71a may extend in the running direction of the base film 10 (four LAs 71 may be arranged in this manner). The length of the extension 71a is, for example, 50 to 150 mm (FIG. 5 shows that the length of the extension 71a is equal to or larger than the maximum length d of the LA 71, which will be described later).2 (The case where the LA71 is the same as the LA71 shown in FIG. 1 is an example.) The LA71 may have a coil shape instead of an open loop shape.

[0060] The LA 71 extends from the fixture 72 toward the base film 10. The LA 71 preferably extends in a direction perpendicular to the fixture 72. The extension length d of the LA 71 from the fixture 72 1 The maximum length d of LA71 in the surface direction of the base film 10 is, for example, 30 to 150 mm. 2 The distance d between the LA71 and the base film 10 is, for example, 50 to 150 mm. 3 (shown in FIG. 6) is, for example, 50 to 200 mm. 1 and separation distance d 3 It is preferable that the extension length d 1 Distance d from 3 The ratio (d 3 / d 1 ) is, for example, 0.5 to 3.5. The number (row number) of LAs 71 spaced apart in the running direction of the base film 10 may be 1, 2 or 3, or may be 4 or more if necessary, depending on the running speed of the base film 10 (i.e., plasma treatment time). The center distance d 4 The center distance d between adjacent LA71 in the width direction of the base film 10 is, for example, 100 to 500 mm. 5 is, for example, 200 to 500 mm. 5 By adjusting the center distance d, the uniformity of the plasma density in the width direction of the base film 10 can be controlled. 4 and center distance d 5 It is preferable that the center distance d is the same as the center distance d. 4 Center distance d 5 The ratio (d 5 / d 4) is, for example, 0.5 to 2.0. The center points of the extensions 71a of the four LAs 71 preferably form a square with the vertices as apexes. Such a set of LAs 71 can generate high density plasma with high in-plane uniformity. For example, a high frequency antenna for plasma generation described in JP 2013-258153 A may be used as the LA 71.

[0061] In this embodiment, the plasma processing chamber C2 further includes a transport roller 53. The transport roller 53 is a main guide roller for transporting the workpiece film W in the plasma processing chamber C2. The transport roller 53 has a temperature adjustment function that can heat or cool the workpiece film W. That is, the transport roller 53 is a transport roller with a temperature adjustment function. When the device Y is in operation, the transport roller 53 transports the base film 10 while contacting the second surface 10b of the base film 10. The LA71 is disposed opposite the transport roller 53. According to the device Y including such a plasma processing chamber C2, in the plasma processing step S2, the transport roller 53 with a temperature adjustment function that contacts the base film 10 can perform plasma processing on the base film 10 while cooling or heating the base film 10. By controlling the temperature of the base film 10, thermal deformation of the base film 10 can be suppressed, and the influence of the thermal deformation on the transport of the base film 10 can be suppressed.

[0062] The PEM device is a device for performing plasma emission monitoring (PEM) during plasma processing, and includes a device body and an optical fiber for collecting light. The tip (one end) of the optical fiber is disposed between the workpiece film W and the LA71 in the direction of separation between them in the plasma processing chamber C2. The other end of the optical fiber is connected to the device body. In addition, a first line L1 with a flow rate control valve for introducing gas into the chamber is connected to the plasma processing chamber C2.

[0063] The connecting chamber C3 is disposed next to the plasma processing chamber C2 in the running direction of the workpiece film W and disposed before the film forming chamber C4. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C3. The connecting chamber C3 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the chamber. When the device Y is in operation, the pressure inside the connecting chamber C3 is maintained at a predetermined pressure between the pressure inside the plasma processing chamber C2 and the pressure inside the film forming chamber C4. This ensures a pressure difference between the plasma processing chamber C2 and the film forming chamber C4.

[0064] The film-forming chamber C4 is disposed next to the connection chamber C3 in the running direction of the workpiece film W. The film-forming chamber C4 is connected to a vacuum pump (not shown) and is configured to be able to adjust the interior of the chamber to a predetermined vacuum level. In the film-forming chamber C4, a film-forming process is carried out as described below.

[0065] In this embodiment, the film forming chamber C4 is a sputtering film forming chamber. The film forming chamber C4 includes a film forming roller 54 and a plurality of sputtering chambers 60 (sputtering chambers 60a to 60e) (a case where the number of sputtering chambers 60 is 5 is illustrated as an example). The film forming roller 54 is a main guide roller for transporting the workpiece film W in the film forming chamber C4. The film forming roller 54 has a temperature adjustment function capable of heating or cooling the workpiece film W. The sputtering chamber 60 is a space partitioned in the film forming chamber C4. The plurality of sputtering chambers 60 are arranged along the circumferential direction of the film forming roller 54. Each sputtering chamber 60 opens toward the film forming roller 54. A cathode 61 is provided in the sputtering chamber 60. A target (not shown) is arranged on the cathode 61 as a film forming material supply material. The target is arranged on the target so as to face the film forming roller 54. Each sputtering chamber 60 is provided with a power supply (not shown) for applying a voltage to the target to generate a glow discharge. Examples of power supplies include a DC power supply, an AC power supply, an MF power supply, an RF power supply, and an MF-AC power supply. An MF-AC power supply refers to an AC power supply with a frequency band of several kHz to several MHz. A required number of second lines (not shown) with flow rate control valves for introducing gas into the chamber are connected to each sputtering chamber 60. In addition, a predetermined number of guide rollers G for guiding the workpiece film W are provided in the film formation chamber C4.

[0066] The connecting chamber C5 and the connecting chamber C6 are arranged in this order between the film forming chamber C4 and the winding chamber R2 in the running direction of the workpiece film W. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C5. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C6. The connecting chamber C5 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the connecting chamber C5. The connecting chamber C6 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the connecting chamber C5. When the device Y is in operation, the pressure inside the connecting chambers C5 and C6 is maintained at a predetermined pressure between the pressure inside the film forming chamber C4 and the pressure inside the winding chamber R2. This ensures a pressure difference between the film forming chamber C4 and the winding chamber R2.

[0067] A plasma processing step and a film forming step are carried out in sequence by the above-described apparatus Y. Specifically, the steps are as follows.

[0068] The workpiece film W is unwound from the unwinding chamber R1. After being unwound from the unwinding chamber R1, the workpiece film W passes through the connecting chamber C1, the plasma processing chamber C2, the connecting chamber C3, the film forming chamber C4, the connecting chamber C5, and the connecting chamber C6 in sequence, and is wound up in the winding chamber R2. The running speed of the workpiece film W is, for example, 0.5 m / min or more, and, for example, 5 m / min or less. In addition, the series of lines from the unwinding chamber R1 to the winding chamber R2 is not open to the atmosphere along the way, and the process is carried out in the line under a reduced pressure atmosphere. The reduced pressure atmosphere is preferably under vacuum. Under vacuum preferably means a reduced pressure atmosphere of 7 Pa or less.

[0069] In the plasma treatment chamber C2, a plasma treatment process is carried out. In the plasma treatment process, in a reduced pressure atmosphere in the plasma treatment chamber C2 (chamber), the first surface 10a of the base film 10 is plasma-treated while detecting the plasma emission intensity. In this embodiment, the plasma treatment is a treatment using inductively coupled plasma of an oxygen-containing gas (oxygen-LAICP treatment) generated by applying high-frequency power to the LA71. More specifically, the process is as follows.

[0070] During plasma processing, oxygen is supplied into the plasma processing chamber C2 through the first line L1. In addition to oxygen, an inert gas may be supplied into the plasma processing chamber C2. Examples of the inert gas include argon, krypton, and xenon. The oxygen concentration of the gas (oxygen-containing gas) in the plasma processing chamber C2 is preferably 30% by volume or more, more preferably 50% by volume or more, even more preferably 80% by volume or more, even more preferably 90% by volume or more, even more preferably 95% by volume or more, and particularly preferably 100% by volume. When the oxygen concentration is equal to or more than the lower limit, high-density oxygen plasma can be generated. This is useful for forming nanometer-order fine irregularities on the first surface 10a of the base film 10 and for highly activating the first surface 10a by cleaning it.

[0071] The pressure (first pressure) in the plasma treatment chamber C2 during plasma treatment is preferably 0.1 Pa or more, more preferably 0.2 Pa or more, even more preferably 0.3 Pa or more, and also preferably 7 Pa or less, more preferably 5 Pa or less, even more preferably 3 Pa or less. When the first pressure is equal to or more than the lower limit, a plasma environment of sufficient density for surface modification treatment of the first surface 10a of the substrate film 10 can be formed in the plasma treatment chamber C2 in the plasma treatment. When the first pressure is equal to or less than the upper limit, thermal damage to the first surface 10a caused by excessively high-density plasma can be suppressed in the plasma treatment, and excessive roughening of the first surface 10a can be suppressed. Suppression of excessive roughening helps to suppress a decrease in the mechanical strength of the first surface 10a. The first pressure can be adjusted by the amount of oxygen gas supplied into the plasma treatment chamber C2.

[0072] The frequency of the high frequency power applied to the LA71 during the plasma treatment is preferably 1 MHz or more, more preferably 5 MHz or more, and even more preferably 10 MHz or more, and is also preferably 100 MHz or less, more preferably 80 MHz or less, and even more preferably 60 MHz or less. When the frequency is equal to or more than the lower limit, the plasma discharge can be stabilized while increasing the plasma current density in the plasma treatment. When the frequency is equal to or less than the upper limit, the antenna potential can be suppressed, and therefore damage to the base film 10 caused by the plasma can be suppressed. Moreover, the high frequency power is preferably 0.1 kW or more, more preferably 0.3 kW or more, and even more preferably 1.0 kW or more, and is also preferably 10 kW or less, more preferably 8 kW or less, and even more preferably 6 kW or less. When the high frequency power is equal to or more than the lower limit, a high density plasma environment can be formed in the plasma treatment chamber C2 in the plasma treatment by inductively coupled plasma. When the high frequency power is equal to or less than the upper limit, excessive damage to the base material caused by the plasma can be suppressed.

[0073] In the plasma treatment step, the plasma emission intensity during the plasma treatment is preferably monitored by a PEM device, and the amount of oxygen gas introduced, the high frequency power, the travel speed, and the like are controlled based on the monitoring results.

[0074] In the plasma treatment step, the plasma current density at the intermediate position between the LA71 and the substrate film 10 is preferably 1.0 mA / cm 3 More preferably, 2.0 mA / cm 3 More preferably, 3.0 mA / cm 3 More than 10 mA / cm 3 Less than or equal to 8mA / cm 3 Less than 4 mA / cm, more preferably 3The plasma treatment using the inductive coupling method using a low inductance antenna can achieve a higher plasma current density (for example, a plasma density about 100 times higher) than the plasma treatment using the capacitive coupling method. When the plasma current density is equal to or higher than the lower limit, sufficient plasma oxygen particles can be secured in the plasma treatment chamber C2 during the plasma treatment, and the first surface 10a of the base film 10 can be appropriately modified. When the plasma current density is equal to or lower than the upper limit, damage to the first surface 10a caused by excessively high density plasma oxygen particles can be suppressed during the plasma treatment. Methods for adjusting the plasma current density include, for example, adjusting the amount of oxygen gas introduced into the plasma treatment chamber C2, adjusting the frequency of the high-frequency power in the high-frequency power source, and adjusting the magnitude of the applied power.

[0075] In the film formation step, following the plasma treatment step, an adhesive layer 21 and an inorganic layer 22 are successively formed on the first surface 10a of the base film 10 by a sputtering method in a reduced pressure atmosphere. The reduced pressure atmosphere is preferably a vacuum.

[0076] In the sputtering method, a sputtering gas (inert gas) is introduced into each sputtering chamber 60 through one second line, while a negative voltage is applied to a target (film forming material) arranged on a cathode 61 in the sputtering chamber 60. This generates a glow discharge to ionize gas atoms, and the gas ions collide with the target surface at high speed, ejecting the target material from the target surface, and depositing the ejected target material on the workpiece film W. Examples of sputtering gases include argon, krypton, and xenon.

[0077] When the deposition material is a metal oxide, the sputtering method may be a reactive sputtering method. In the reactive sputtering method, oxygen (reactive gas) is introduced into the sputtering chamber 60 in addition to the sputtering gas. The oxygen is introduced into the sputtering chamber 60 through another second line. In the reactive sputtering method, the target is made of, for example, a metal in the metal oxide that forms each layer.

[0078] In the sputtering method, the pressure (second pressure) in the sputtering chamber 60 is, for example, 0.1 to 5.0 Pa depending on the type of layer to be formed. The film formation temperature (the temperature of the workpiece film W adjusted by the film formation roller 54) is, for example, -10°C to 150°C.

[0079] In the film formation process, first, an adhesive layer 21 is formed on the substrate film 10 by a sputtering method in the sputtering chamber 60a. When an ITO layer is formed as the adhesive layer 21, an ITO target is used as a target disposed on the cathode 61 in the sputtering chamber 60a. Then, sputtering is performed while introducing argon into the sputtering chamber 60a. Alternatively, reactive sputtering is performed while introducing argon and oxygen into the sputtering chamber 60a.

[0080] In the film formation step, next, an inorganic layer 22 is formed on the adhesive layer 21 by a sputtering method in at least one sputtering chamber selected from the sputtering chambers 60b to 60e. For example, when forming an inorganic layer 22 (FIG. 2) as an anti-reflection layer, a high refractive index layer 22a is formed on the adhesive layer 21 in the sputtering chamber 60b, a low refractive index layer 22b is formed on the high refractive index layer 22a in the sputtering chamber 60c, a high refractive index layer 22c is formed on the low refractive index layer 22b in the sputtering chamber 60d, and a high refractive index layer 22d is formed on the high refractive index layer 22c in the sputtering chamber 60e.

[0081] In the device Y, after the plasma treatment process and the film forming process, the laminated film X as the workpiece film W passes through the connecting chambers C5 and C6 and reaches the winding chamber R2, where it is wound up by the winding roller 52.

[0082] In this manner, a long laminate film X can be produced. EXAMPLES

[0083] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".

[0084] Example 1 The laminated film of Example 1 was produced by carrying out the following steps in order.

[0085] First, a hard coat layer was formed on one side of a triacetyl cellulose (TAC) film as a resin film to prepare a substrate film (preparation step). Specifically, first, 100 parts by mass (solid content equivalent value) of a butyl acetate solution of an ultraviolet-curable acrylic urethane resin (product name "Luxidia 17-806", solid content concentration 80% by mass, manufactured by DIC Corporation), 5 parts by mass of a photopolymerization initiator (product name "Omnirad907", manufactured by IGM Resins), 0.03 parts by mass of a leveling agent (product name "GRANDIC PC4100", manufactured by DIC Corporation), and butyl acetate as a solvent were mixed to prepare a first resin composition with a solid content concentration of 75% by mass. Next, cyclopentanone was added as an additional solvent to the first resin composition to prepare a second resin composition with a solid content concentration of 50% by mass. Meanwhile, a long TAC film (length 100 m, width 340 mm, thickness 40 μm) was prepared. Next, the second resin composition was applied to one side of the TAC film to form a coating film. Next, this coating film was dried by heating and then cured by ultraviolet light irradiation. As a result, a hard coat (HC) layer having a thickness of 5 μm was formed on the TAC film. The heating temperature was 100° C., and the heating time was 60 seconds. For ultraviolet light irradiation, a high-pressure mercury lamp was used as a light source, and ultraviolet light with a wavelength of 365 nm was irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm. 2 In this manner, a TAC film with an HC layer was prepared as a substrate film.

[0086] Next, while the base film was transported in a vacuum by a roll-to-roll method, a plasma treatment process and a subsequent film formation process were performed on the base film (roll-to-roll process). For the plasma treatment process and the film formation process, an apparatus (first apparatus) capable of performing a roll-to-roll process on the work film was used. The first apparatus includes a payout chamber, a plasma treatment chamber, a film formation chamber, and a winding chamber. The payout chamber, the plasma treatment chamber (first plasma treatment), the film formation chamber, and the winding chamber are arranged in this order and communicate with each other. The payout chamber includes a payout roller. A roll of the base film was set on the payout roller as the work film. The plasma treatment chamber includes a transport roller with a temperature control function (transport roller 53 in FIG. 4) and four low inductance antennas (LA71 in FIG. 5 and FIG. 6) covered with a cover block (cover block 73 in FIG. 6) as shown in FIG. 5 and FIG. 6. Each low inductance antenna has an extension portion (extension portion 71a in FIG. 5) parallel to the base film. The four low inductance antennas have an extension length d 1 is 88 mm, and the maximum length d 2 (Length of extension) is 100 mm, and the separation distance d 3 is 112 mm, and the center distance d 4 is 290 mm, and the center distance d 5The distance between the substrate film and the cover block is 280 mm (FIGS. 5 and 6). Each low inductance antenna is electrically connected to a high-frequency power source (RF power source, frequency 13.56 MHz) via an impedance matcher outside the plasma processing chamber. The separation distance d' between the substrate film traveling in the plasma processing chamber and the cover block is 100 mm. The film formation chamber is a sputtering film formation chamber, and includes a film formation roller (film formation roller 54 in FIG. 4) and first and second sputtering chambers (sputtering chambers 60a, 60b in FIG. 4). Each sputtering chamber is a partitioned space within the film formation chamber. The first and second sputtering chambers are arranged in this order along the circumferential direction of the film formation roller in the traveling direction of the substrate film. Each sputtering chamber includes a cathode arranged opposite the film formation roller. A required number of second lines (not shown) with flow rate control valves for introducing gas into the chamber are connected to each sputtering chamber. The winding chamber includes a winding roller.

[0087] In the roll-to-roll process, the HC surface (first surface) of the base film was plasma-treated in the plasma treatment chamber (plasma treatment step). The running speed of the base film (film running speed) was 0.5 m / min. The temperature of the temperature-adjustable transport roller was -8°C. The conditions for the plasma treatment were as follows:

[0088] The ultimate vacuum level of the plasma processing chamber is 1.0×10 -4 After evacuating the inside of the apparatus until the pressure inside the plasma treatment chamber reached 0.5 Pa, oxygen gas was introduced into the plasma treatment chamber to set the pressure inside the plasma treatment chamber to 0.5 Pa. By applying high frequency power of 5.0 kW from a high frequency power supply to four low inductance antennas, inductively coupled plasma of an oxygen-containing gas was formed around the antennas (the surface of the HC layer of the base film was treated with this plasma).

[0089] In the film formation chamber, an adhesive layer and an inorganic layer were successively formed on the substrate film after the plasma treatment (film formation process: adhesive layer formation process and inorganic layer formation process). Specifically, while the substrate film was cooled and transported by the film formation roll in the film formation chamber, an adhesive layer was formed on the HC layer of the substrate film in the first sputtering chamber, and an inorganic layer was formed on the adhesive layer in the second sputtering chamber. The film formation temperature (temperature of the film formation roll) was set to -8°C. More specifically, it is as follows.

[0090] In the first sputtering chamber, a 5 nm thick ITO layer was formed as an adhesive layer by sputtering (adhesive layer formation process). In this process, the ultimate vacuum in the film formation chamber was 1.0×10 -4 After the chamber was evacuated to a vacuum of 0.3 Pa, argon was introduced as an inert gas into the first sputtering chamber, and the pressure in the first sputtering chamber was set to 0.3 Pa. As the target, a sintered body of indium oxide and tin oxide (ITO with a tin oxide concentration of 10 mass %) was used. As the power source for applying a voltage to the target, a DC power source was used. The discharge power was 1.0 kW.

[0091] In the second sputtering chamber, a 20 nm thick SiO 2 A layer was formed as an inorganic layer. In this process, after the deposition chamber was evacuated as described above, argon as an inert gas and oxygen as a reactive gas were introduced into the second sputtering chamber, and the pressure in the second sputtering chamber was set to 0.3 Pa. The amount of oxygen introduced per 100 parts by volume of argon introduced into the second sputtering chamber was 30 parts by volume. A Si target was used as the target. A MF-AC power supply (60 kHz) was used as the power supply for applying a voltage to the target. The discharge power was 3.0 kW.

[0092] In this manner, the laminated film of Example 1 was produced. The laminated film of Example 1 was a substrate film with an HC layer, an adhesive layer (ITO) on the HC layer, and an inorganic layer (SiO 2) The substrate film of the laminated film of Example 1 has a plasma-treated HC layer surface. This plasma treatment is a treatment by inductively coupled plasma using an oxygen-containing gas, which is generated by applying high-frequency power to a low-inductance antenna (oxygen-LAICP treatment).

[0093] Example 2 The laminated film of Example 2 was produced in the same manner as the laminated film of Example 1, except for the following: The running speed of the base film was 1.0 m / min, and the high-frequency power applied in the plasma treatment step was 3.5 kW.

[0094] Comparative Example 1 First, in the same manner as in the preparation step of Example 1, an HC layer was formed on one side of a TAC film to prepare a base film (TCA film / HC layer).

[0095] Next, while the base film was transported in a vacuum by a roll-to-roll method, a plasma treatment process and a subsequent film formation process were performed on the base film (roll-to-roll process). A second device capable of performing a roll-to-roll process on the work film was used for the plasma treatment process and the film formation process. The second device has the same configuration as the first device, except that it has a second plasma treatment chamber instead of the first plasma treatment. The second plasma treatment chamber has a cathode electrode and an anode electrode (both rectangular electrodes made of SUS304) as a pair of flat electrodes for generating plasma. The pair of flat electrodes are arranged parallel to the base film passing through the second plasma treatment chamber with a gap of 50 mm. The anode electrode is arranged at a position 35 mm away from the base film passing through the second plasma treatment chamber and is grounded outside the plasma treatment chamber. The cathode electrode is arranged to face the HC layer surface of the base film, and is electrically connected to a high-frequency power source (RF power source, 13.56 MHz) via an impedance matching device. The length of each electrode facing the base film in the film running direction is 110 mm, and the length in the width direction is 430 mm.

[0096] In the roll-to-roll process, the HC surface (first surface) of the base film was plasma-treated (bombardment treatment) in the second plasma treatment chamber. The running speed of the base film (film running speed) was 1.0 m / min. The conditions for the plasma treatment were as follows:

[0097] The ultimate vacuum in the second plasma processing chamber is 1.0×10 -4 After evacuating the inside of the device until the pressure reached 0.5 Pa, argon was introduced into the second plasma treatment chamber, and the pressure in the plasma treatment chamber was set to 0.5 Pa. Capacitively coupled plasma (CCP) was generated by applying a power of 550 W between the planar electrodes using a high-frequency power source. In this plasma environment, the HC layer surface of the base film was bombarded with argon ions (Ar-BB treatment).

[0098] In the film formation chamber, an adhesive layer and an inorganic layer were formed in this order on the substrate film after the plasma treatment in the same manner as described above in relation to Example 1.

[0099] In this manner, the laminated film of Comparative Example 1 was produced. The laminated film of Comparative Example 1 was a substrate film with an HC layer, an adhesive layer (ITO) on the HC layer, and an inorganic layer (SiO 2 ) In the base film of the laminated film of Comparative Example 1, the surface of the HC layer is plasma-treated. This plasma treatment is an ion bombardment treatment (Ar-BB treatment) by capacitively coupled plasma using an argon-containing gas.

[0100] Comparative Example 2 A laminated film of Comparative Example 2 was produced in the same manner as the laminated film of Example 1, except for the following: The running speed of the base film was 1.0 m / min, and the high-frequency power applied in the plasma treatment step was 2.0 kW.

[0101] <Surface free energy> For each of the laminate films of Examples 1 and 2 and Comparative Examples 1 and 2, the surface free energy of the plasma-treated surface of the base film was determined as follows.

[0102] First, the substrate film after plasma treatment and before the formation of the adhesive layer in the manufacturing process of the laminated film was sampled, and a sample film of a predetermined size was cut out from the substrate film. Next, the sample film was placed on a horizontally arranged slide glass. Specifically, the sample film was placed on the slide glass so that the plasma-treated surface (HC layer surface) of the sample film was facing up. Next, in an atmosphere of 23°C and relative humidity of 50%, 2 μL of a predetermined liquid was dropped onto the plasma-treated surface of the sample film on the slide glass to form a droplet (droplet formation). Next, the contact angle of the droplet with respect to the sample film surface (plasma-treated surface) was measured using a contact angle meter (product name "DMs-401", manufactured by Kyowa Interface Science Co., Ltd.) (contact angle measurement). Water (H 2 O), methylene iodide (CH 2 I 2 ) and 1-bromonaphthalene were used. For each liquid, a series of steps including the formation of a droplet and the subsequent measurement of the contact angle was carried out five times. The measurements were carried out within 24 hours after the plasma treatment of the substrate film. The average of the five measurements for each liquid was taken as the contact angle for that liquid. In this manner, the contact angle θw of water, the contact angle θi of methylene iodide, and the contact angle θb of 1-bromonaphthalene for the sample film were obtained.

[0103] Next, for each sample film, the contact angle of water θw, the contact angle of methylene iodide θi, and the contact angle of 1-bromonaphthalene θb are used to solve the three simultaneous equations in the Kitazaki-Hata theory to obtain the surface free energy γ = γ d +γ p +γ h In the formula, γ d ,γ p ,γ h The Kitazaki-Hata theory is described, for example, in the Journal of the Japan Adhesion Association, Vol. 8, No. 3, p. 131-141 (1972). d is the dispersion component of the surface free energy, and γ p is the polar component of the surface free energy, and γ his the hydrogen bonding component of the surface free energy, and γ d ,γ p ,γ h The value (γ) obtained by adding up the above values ​​was determined as the surface free energy of the plasma-treated surface of the sample film. The dispersion component γ d is 29.1 mN / m, and the polar component γ p is set to 1.3 mN / m, and the hydrogen bond component γ h The dispersion component γ in the surface free energy of methylene iodide was d is 46.8mN / m, and the polar component γ p is set to 4.0 mN / m, and the hydrogen bond component γ h was set to 0.0 mN / m. The dispersion component γ in the surface free energy of 1-bromonaphthalene d is 44.4 mN / m, and the polar component γ p is set to 0.1 mN / m, and the hydrogen bond component γ h was set to 0.0 mN / m. The surface free energy (mN / m) of the plasma-treated surface of the sample film is shown in Table 1.

[0104] <Surface roughness> The surface roughness of the first surface of the base film was examined for each of the laminated films of Examples 1 and 2 and Comparative Examples 1 and 2. Specifically, first, the base film after plasma treatment and before the formation of the adhesive layer in the manufacturing process of the laminated film was sampled, and the surface roughness Sa (arithmetic mean height based on ISO 25178) of the first surface (HC layer surface) of the base film was measured in an observation image of 1 μm square using an atomic force microscope (product name "Dimention Edge", manufactured by Bruker). In this measurement, the measurement mode was set to tapping mode, and an antimony-doped Si cantilever (product name "RTESP-300", manufactured by Bruker) was used as a probe. The measurement results are shown in Table 1.

[0105] <Interface length ratio> The ratio of the second interface length L2 of the interface between the adhesive layer and the inorganic layer to the first interface length L1 of the interface between the base film and the adhesive layer in a cross-sectional view was examined for each of the laminate films of Examples 1 and 2 and Comparative Examples 1 and 2. Specifically, the ratio is as follows.

[0106] First, a sample for observing the cross section of the laminated film was prepared by the FIB microsampling method. In the FIB microsampling method, an FIB device (name "FB2200", manufactured by Hitachi) was used, and the initial acceleration voltage was set to 40 kV, and the finishing acceleration voltage was set to 10 kV. Next, the cross section of the sample was observed by FE-TEM. In this observation, an FE-TEM device (name "JEM-2800", manufactured by JEOL) was used, and the acceleration voltage was set to 200 kV. FIG. 7 shows an observation image of the cross section of the sample of Example 1 as an example. In the observation image of Example 1, the HC layer 11 of the base film 10, the adhesive layer 21, and the inorganic layer 22 were observed. FIG. 8 shows an observation image of the cross section of the sample of Comparative Example 1 as another example. In the observation image of Comparative Example 1, the HC layer 11' of the base film 10', the adhesive layer 21', and the inorganic layer 22' were observed. Next, the observed image was analyzed by image processing software ImageJ. As a result, the first interface length L1 of the interface between the base film 10 (10') and the adhesive layer 21 (21') and the second interface length L2 of the interface between the adhesive layer 21 (21') and the inorganic layer 22 (22') in a predetermined image range in the observed image (cross-sectional view) were obtained. Then, the ratio (L2 / L1) of the second interface length L2 to the first interface length L1 was calculated. The values ​​are shown in Table 1.

[0107] <Adhesion> For each of the laminate films of Examples 1 and 2 and Comparative Examples 1 and 2, the following first and second tests were carried out to examine the adhesion of the inorganic layer.

[0108] Test 1: First, the substrate film side of the laminated film was fixed to a glass plate. Next, the inorganic layer of the laminated film on the glass plate was irradiated with light at a temperature of 85° C., a relative humidity of 45%, and an irradiation intensity (integrated illuminance at 290 nm to 450 nm) of 150 mW / cm 2 2The specimen was exposed to light from a metal halide lamp for 32.5 hours under the above conditions (accelerated weather resistance test). This test was carried out using Iwasaki Electric's "Eye Super UV Tester SUV-W161."

[0109] Test 2: First, eleven parallel first incisions (1 mm apart) extending linearly in a first direction and eleven parallel second incisions (1 mm apart) extending linearly in a second direction perpendicular to the first direction were made with a cutter knife in the inorganic layer and adhesive layer of the laminated film on the glass plate after the first test, and 100 grids were formed by the first and second incisions. Next, isopropyl alcohol was continuously dripped at 2 mL / min on the 100 grid areas of the laminated film while a polyester wiper (trade name "Anticon Gold", manufactured by Sanplatec Co., Ltd.) was slid over the wiper contact surface of 20 mm x 20 mm, a load of 1.5 kg / 20 mm, a sliding speed of 50 mm / sec, and 1000 reciprocations. Next, 0.25 mm out of the 100 grids were cut. 2 The number of squares in which the above peeling occurred was counted, and the counted number was then divided by 100 to calculate the peeling rate (%).

[0110] A peeling rate of 5% or less was evaluated as “good,” and a peeling rate of more than 5% was evaluated as “bad.” The results are shown in Table 1.

[0111] [evaluation] In the laminated film of Comparative Example 1, the HC layer of the base film does not contain particles. Therefore, as shown in FIG. 8, the surface of the base film 10' (the surface on the adhesive layer 21' side) does not have unevenness caused by particles. In addition, the plasma treatment in the manufacturing process of the laminated film of Comparative Example 1 is, as described above, an ion bombardment treatment (Ar-BB treatment) by capacitively coupled plasma using argon-containing gas. The Ar-BB treatment cannot activate the base film surface compared to the oxygen-LAICP treatment. This is reflected in the fact that the surface free energy of the plasma-treated surface of the base film in Comparative Example 1 is smaller than the surface free energy of the plasma-treated surface of the base film in Example 1. In addition, the inventors have found that the Ar-BB treatment cannot roughen the base film surface compared to the oxygen-LAICP treatment. In such a laminated film of Comparative Example 1, the ratio (L2 / L1) of the second interface length L2 to the first interface length L1 was significantly lower than 1.10. Therefore, the adhesiveness of the inorganic layer could not be ensured in the laminated film of Comparative Example 1.

[0112] In the laminated film of Comparative Example 2, the HC layer of the base film does not contain particles, so the surface of the base film (the surface on the adhesive layer side) does not have unevenness caused by particles. In addition, the plasma treatment in the manufacturing process of the laminated film of Comparative Example 2 is a treatment by inductively coupled plasma using an oxygen-containing gas (oxygen-LAICP treatment) generated by applying high-frequency power to a low-inductance antenna as described above, but the applied high-frequency power is insufficient. In such a laminated film of Comparative Example 2, the ratio (L2 / L1) of the second interface length L2 to the first interface length L1 was significantly lower than 1.10. Therefore, the adhesiveness of the inorganic layer could not be ensured in the laminated film of Comparative Example 2.

[0113] In the laminated film of Example 1, the HC layer of the base film does not contain particles. Therefore, as shown in FIG. 7, the surface of the base film 10 (the surface on the adhesive layer 21 side) does not have unevenness caused by particles. However, the plasma treatment in the manufacturing process of the laminated film of Example 1 is a treatment by inductively coupled plasma using an oxygen-containing gas generated by applying high-frequency power to a low-inductance antenna (oxygen-LAICP treatment) as described above, and the applied high-frequency power is sufficiently large. According to such oxygen-LAICP treatment, the surface of the base film can be roughened with fine unevenness on the nanometer order, and the surface of the base film can be activated, compared with the Ar-BB treatment and the oxygen-LAICP treatment with insufficient applied power. This is shown in the surface of the inorganic layer 22 side of the adhesive layer 21 formed on the base film 10, as shown in FIG. On the surface of the adhesive layer, unevenness is formed that originates from the fine unevenness on the highly active surface of the base film 10 and grows from the fine unevenness during the film formation process of the adhesive layer. Specifically, in the laminate film of Example 1, the ratio (L2 / L1) of the second interface length L2 to the first interface length L1 was 1.10 or more. Therefore, in the laminate film of Example 1, the adhesion of the inorganic layer was ensured.

[0114] In the laminated film of Example 2, the HC layer of the base film does not contain particles. Therefore, like the laminated film of Example 1, the surface of the base film 10 (the surface on the adhesive layer 21 side) does not have unevenness due to particles. However, like the plasma treatment in Example 1, the plasma treatment in the manufacturing process of the laminated film of Example 2 is a treatment by inductively coupled plasma using an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna (oxygen-LAICP treatment), and the applied high-frequency power is sufficiently large. According to such oxygen-LAICP treatment, the surface of the base film can be roughened with fine unevenness on the nanometer order and the surface of the base film can be activated, compared with the Ar-BB treatment and the oxygen-LAICP treatment with insufficient applied power. On the surface of the adhesive layer, unevenness is formed that has grown from the fine unevenness of the highly active surface of the base film 10 as a starting point during the film formation process of the adhesive layer. Specifically, in the laminated film of Example 2, the ratio (L2 / L1) of the second interface length L2 to the first interface length L1 was 1.10 or more. Therefore, in the laminate film of Example 2, the adhesion of the inorganic layer was ensured.

[0115] [Table 1] [Explanation of symbols]

[0116] X Laminated Film H Thickness direction D plane direction 10. Base film 10a 1st page 10b 2nd side 11 Resin film 12 Cured resin layer 21 Adhesion layer 22 Inorganic layer 22a, 22c High refractive index layer 22b, 22d Low refractive index layer

Claims

1. A laminated film comprising a base film, an adhesive layer on the base film, and an inorganic layer on the adhesive layer, The base film includes a resin film and a cured resin layer, The content of inorganic oxide particles in the cured resin layer is 20% by mass or less, A laminate film, in which, in a cross-sectional view in the thickness direction, a ratio of a second interface length at an interface between the adhesive layer and the inorganic layer to a first interface length at the interface between the base film and the adhesive layer is 1.10 or more.

2. 2. The laminated film according to claim 1, wherein said ratio is 2.0 or less.

3. The laminated film according to claim 1 , wherein the adhesive layer has a thickness of 1 nm or more and 50 nm or less.

4. 2. The laminated film according to claim 1, wherein the adhesive layer is an inorganic oxide film containing at least one element selected from the group consisting of Si, In, Al, Sn, Ti, Zr and Nb.

5. The laminate film according to claim 1 , wherein the inorganic layer comprises a conductive layer.

6. The laminate film according to claim 1 , wherein the inorganic layer includes an anti-reflection layer, the anti-reflection layer including a plurality of transparent inorganic oxide films laminated in a thickness direction.